Conquering knowledge exchange barriers with age differences: A stress appraisal perspective on the consequences of upward social comparisons - Laura Rinker; Ulrike Fasbender; Fabiola H. Gerpott; Anne Burmeister (Journal of Occupational and Organizational Psychology, 2024)
AbstractKnowledge exchange is crucial for organizations, but interpersonal dynamics can entail stress, affecting whether and how knowledge flows. Integrating social comparison and stress appraisal research, we propose that upward social comparison can be appraised as challenging or hindering. We suggest a dual pathway model involving an approach pathway via challenge appraisal and an avoidance pathway via hindrance appraisal with consequences on three knowledge exchange behaviours (i.e., knowledge sharing, knowledge seeking and knowledge hiding). Additionally, we examine age differences (vs. no age differences) to the comparison target as a buffer. We conducted two preregistered experimental online studies with employees (NStudy~10.167em=0.167em206, NStudy 20.167em=0.167em414), utilizing a 2 (social comparison; upward, lateral)0.167em0.167em3 (target age; younger, same-age, older) between-subject design. Participants received bogus task performance feedback (Study 1: cognitive ability test; Study 2: typing ability test). Both studies show that upward social comparison (but not other social comparison directions) fosters knowledge hiding via hindrance appraisal. This effect is weakened by an age difference (vs. no age difference) to the comparison target. However, our results do not support the approach pathway via challenge appraisal. Our research highlights social pitfalls in knowledge exchange and emphasizes the benefits of age differences between colleagues.
Keywords: 650; age difference; challenge-hindrance stress appraisal theory; knowledge exchange; social comparison theory; upward social comparison